2019
DOI: 10.1186/s13071-019-3601-x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid assessment of faecal egg count and faecal egg count reduction through composite sampling in cattle

Abstract: Background Faecal egg counts (FEC) and the FEC reduction test (FECRT) for assessing gastrointestinal nematode (GIN) infection and efficacy of anthelmintics are rarely carried out on ruminant farms because of the cost of individual analyses. The use of pooled faecal samples is a promising method to reduce time and costs, but few studies are available for cattle, especially on the evaluation of different pool sizes and FECRT application. Methods A study was conducted to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 22 publications
2
24
0
2
Order By: Relevance
“…In addition, the Mini-FLOTAC and Fill-FLOTAC are user-friendly devices (i.e., no special equipment such as a centrifuge, or trained technicians are required), so they can be used directly by veterinarians or farmers in the field (pen-side use) (8). Recently, Rinaldi et al (16) showed that the use on farm of a portable Mini-FLOTACkit (composed of 2 Fill-FLOTAC, 2 Mini-FLOTAC, the salt to prepare the flotation solution and all the material necessary to perform the Mini-FLOTAC technique) ( Figure 2) and a portable microscope is a swift and cost-effective procedure for FEC of GIN in cattle. To further reduce time and costs, a pooling strategy has been successfully developed and validated for cattle and sheep feces using the Mini-FLOTAC technique (9,11,12,16).…”
Section: Strengthsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the Mini-FLOTAC and Fill-FLOTAC are user-friendly devices (i.e., no special equipment such as a centrifuge, or trained technicians are required), so they can be used directly by veterinarians or farmers in the field (pen-side use) (8). Recently, Rinaldi et al (16) showed that the use on farm of a portable Mini-FLOTACkit (composed of 2 Fill-FLOTAC, 2 Mini-FLOTAC, the salt to prepare the flotation solution and all the material necessary to perform the Mini-FLOTAC technique) ( Figure 2) and a portable microscope is a swift and cost-effective procedure for FEC of GIN in cattle. To further reduce time and costs, a pooling strategy has been successfully developed and validated for cattle and sheep feces using the Mini-FLOTAC technique (9,11,12,16).…”
Section: Strengthsmentioning
confidence: 99%
“…Mini-FLOTAC and Fill-FLOTAC, developed by the Unit of Parasitology and Parasitic Diseases of the Department of Veterinary Medicine and Animal Production (University of Naples Federico II), are easy-to-use devices, used in combination to perform the Mini-FLOTAC technique, a multivalent, sensitive, accurate, precise, and reproducible copromicroscopic method (8). Because of these characteristics, these tools have increasingly been employed in FEC and FECRT surveys (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The Mini-FLOTAC is a self-contained device for viewing and counting helminth eggs per gram of feces, under the microscope, after preparation from fecal samples, using the Fill-FLOTAC device (8).…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic methods for GIN include faecal egg count (FEC) techniques that are commonly used in parasitological research and veterinary practice to indirectly assess GIN burdens and determine anthelmintic efficacy/resistance through the faecal egg count reduction test (FECRT) [6]. FEC techniques based on easy-to-use devices with high diagnostic performance in terms of sensitivity, accuracy, precision and reproducibility are suggested to perform reliable and exploitable FEC/FECRT in cattle [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Cornell-Wisconsin, McMaster and FECPAK, and was shown to be more sensitive, accurate and precise for FEC and FECRT of GINs in sheep [7, [9][10][11][12]. Mini-FLOTAC has been also successfully used to perform FEC and FECRT (in the laboratory and on-farm) in cattle [5,7,13,14]. However, only a single study by Paras et al [7] evaluated the recovery rate of GIN eggs by Mini-FLOTAC (compared to…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high sensitivity of FEC and FECM techniques, they are limited by the need for centrifugation of the sample [8] . The FLOTAC method, originally developed for diagnosis of veterinary parasites infections [9] , was later used for the diagnosis of human intestinal helminthes and protozoa infections [10,11] . The mini-FLOTAC technique was then introduced as a reasonable development of FLOTAC for performing multivalent, and qualitative diagnosis of intestinal parasitic infections in human and animal feces.…”
Section: Introductionmentioning
confidence: 99%